Cobalt products from real waste fractions of end of life lithium ion batteries. (May 2016) - Pagnanelli, Francesca; Moscardini, Emanuela; Altimari, Pietro; Abo Atia, Thomas; Toro, Luigi
Highlights: LIB electrodic powders were recovered using pilot scale mechanical treatments. Electrodic powders were leached by sulfuric acid and hydrogen peroxide. Precipitation by pH variation determined the complete abatement of Fe. Solvent extraction was used to remove Mn and to recover Co. Final CoCO3 with 95% was obtained after refining product for Na removal. Abstract: An innovative process was optimized to recover Co from portable Lithium Ion Batteries (LIB). Pilot scale physical pretreatment was performed to recover electrodic powder from LIB. Co was extracted from electrodic powder by a hydrometallurgical process including the following main stages: leaching (by acid reducing conditions), primary purification (by precipitation of metal impurities), solvent extraction with D2EPHA (for removal of metal impurities), solvent extraction with Cyanex 272 (for separation of cobalt from nickel), cobalt recovery (by precipitation of cobalt carbonate). Tests were separately performed to identify the optimal operating conditions for precipitation (pH 3.8 or 4.8), solvent extraction with D2EHPA (pH 3.8; Mn/D2EHPA = 4; 10% TBP; two sequential extractive steps) and solvent extraction with Cyanex 272 (pH 3.8; Cyanex/Cobalt = 4, 10% TBP, one extractive step). The sequence of optimized process stages was finally performed to obtain cobalt carbonate. Products with different degree of purity were obtained depending on the performed purification steps (precipitation with or without solvent extraction). 95% purity was achieved by implementation of the process including the solvent extraction stages with D2EHPA and Cyanex 272 and final washing for sodium removal.